Comparative cytogenetics and chromosomal characteristics of ribosomal DNA in the fish genus Vimba (Cyprinidae) - Rábová, M; Ráb, P; Ozouf-Costaz, C; Ene, C; Wanzeböck, J (Genetica, 2003)
Karyotypic and cytogenetic characteristics of Vimba vimba and V. elongata were investigated using differential staining techniques (sequential C-banding, Ag- and CMA3-staining) and fluorescent in situ hybridization (FISH) with 28S rDNA probe. The diploid chromosome number in both species was 2n = 50 with 8 pairs of metacentrics, 14 pairs of submetacentrics to subtelocentrics and 3 pairs of subtelo- to acrocentrics. The largest chromosome pair of the complements was characteristically subtelo- to acrocentric. The nucleolar organizer regions (NORs) in both species were detected in the telomeres of a single, middle-sized subtelocentric chromosome pair, a pattern common in a number of other Leuciscinae. FISH with rDNA probe produced consistently positive hybridization signals detected in the same regions indicated by Ag-staining and CMA3-fluorescence. The distribution of C-positive heterochromatin was identical in both species, including a conspicuous size polymorphism of heterochromatic blocks in the largest metacentric and subtelo- to acrocentric chromosomal pairs. No heteromorphic sex chromosomes were detected. A single analyzed individual of V. melanops possessed the same karyotype and NOR phenotype as V. vimba and V. elongata. The apparent karyotype homogeneity and chromosomal characteristics of ribosomal DNA in all three species of the genus Vimba is consistent to that found in most other representatives of the European leuciscine cyprinid fishes.
Keywords: cytogenetické vyšetření; Silver Staining; Animals; Karyotyping; barvení stříbrem; Cyprinidae; hybridizace in situ fluorescenční; organizátor jadérka; ribozomální DNA; zvířata; DNA, Ribosomal; In Situ Hybridization, Fluorescence; Nucleolus Organizer Region; Cytogenetic Analysis; Chromosome Banding; karyotypizace; pruhování chromozomů